International higher education and soft power in Newly Industrialised Countries 2008-2018 - Puebla Mora, Martha Flor (2021)
Soft power is an ability developed by countries to make others do what otherwise they would not, using tools such as attraction, persuasion/influence and setting agendas according to their national goals. Developed and developing countries use different tools to build soft power capabilities in different ways. This thesis investigates how International Higher Education (IHE) produces soft power in Newly Industrialised Countries (NICs), focusing on three case studies: Brazil, Malaysia and Mexico. This is a multidisciplinary study where International Relations, Politics and Education fields of study collide to increase our understanding of soft power. This research argues that Higher Education Institutions (HEIs), research centres, associations of universities and other non-governmental actors become agents of soft power using diplomacy mechanisms, challenging the traditional soft power understandings.